'On the Line': a report on shifting collaborations around clotheslines. Issue 3 (3rd May 2016) - Ossman, Susan
Abstract: This vignette tells the story of 'On the Line', a Riverside, California series of exhibitions, performances, research and participatory interventions that focus on clotheslines to probe divisions of life and art, gender and culture and generation. Who does your laundry? What does an electric dryer indicate about changing relationships to nature? How do movements and conversations around laundry lines differ across the world? Each event has associated art and ethnography differently, building on earlier work to develop varied modes of spectatorship, participation, research and dialogue. The programme started with my work: first a painting, then in 2013 the first 'On the Line' exhibition. Artists, anthropologists and graduate students developed a 'critique' and then a 'remake' of that exhibition called 'On the Line: A Second look'. The circle of collaborative research and practice widened and produced 'Hanging Out' in 2015. That exhibition was developed as a site for fieldwork, collaboration and performance, leading to a project to expand the widening circle of participation with outdoor pop-up exhibitions and performances in neighbourhoods across the city in 2016. I propose an engaged, insider's account of the process to suggest how focusing on a simple, nearly universal practice across scenes designed to shift participants' roles and positions, brought something of the estrangement and iterative qualities of fieldwork to collaborative practices and public discussions.